NEEDS ANALYSIS IN EFL READING CLASS: A STUDY TO PROMOTE LEARNER AUTONOMY THROUGH SELF-ASSESSMENT - Taufiqulloh Taufiqulloh; Sri Wardhani; Anin Eka Sulistyawati (University of Kuningan, 2018)
Teaching EFL reading to the students at colleges or universities requires an appropriate technique that enables students to enhance their achievement as well as to develop their sense of independent learning. This is also to respond to the current trend of that the focus of ELT today is creating learners who are not only competent but also dependent or autonomous in learning. This study is aimed at exploring the needs of both lecturers and students on EFL reading class. The method used was descriptive-qualitative. It was conducted at the English Education Department, Faculty of Teacher Training and Education, Pancasakti University Tegal, from April to June 2018. The participants of this study were 64 students of the fourth semester in the department attending EFL reading class and 4 EFL lecturers. The data were collected using triangulation. The instruments used were a questionnaire, classroom observation, and interview. The results showed that the instruction and assessment were still teacher-centered, the learning materials and the method did not meet the students’ needs, the selection of the materials was not in line with the students’ level of competence, the students were given fewer opportunities to explore and share their ideas with others, etc. The result also showed that both students and lecturers agreed that learning EFL reading through self-assessment could be an alternative learning model or technique to cope with the situations.Keywords: needs analysis; EFL reading; learner autonomy; self-assessment.